KOMPARASI KONSEP SISTEM PRESIDENSIAL ANTARA UUD 1945 DAN UUD NRI TAHUN 1945 - Efriza . (Jurnal Ilmu dan Budaya, 2016)
This article discusses the president-parliament relations, especially its main legislative and executive in a presidential system who often get caught up in the conflict between institution. This article argues, that is the originial of UUD 1945 amendment aim that, Indonesia adheres to a presidential system, but its also contain elements of a parliamentary system, the result is a system of government that is not unusual. The study discover that the Presidential not run optimally, not only from the construction of the constitution and legislation but is also affected by the combination of multiparty, and the President-Parliament relations in practice. Underlying theory perspective is the theoritical limitation of power and the presidential system; to comprehend the concept of a presidential system and its implications.